Finding location-specific aggregated air quality index with smartphone images using deep convolutional neural network - Mondal, Joyanta Jyoti; Rhidi, Nowsin Kabir (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.